2020
DOI: 10.1186/s12864-020-07059-y
|View full text |Cite
|
Sign up to set email alerts
|

SWI/SNF complexes act through CBP-1 histone acetyltransferase to regulate acute functional tolerance to alcohol

Abstract: Background SWI/SNF chromatin remodeling genes are required for normal acute responses to alcohol in C. elegans and are associated with alcohol use disorder in two human populations. In an effort to discover the downstream genes that are mediating this effect, we identified SWI/SNF-regulated genes in C. elegans. Results To identify SWI/SNF-regulated genes in adults, we compared mRNA expression in wild type and swsn-1(os22ts) worms und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
2
6
0
Order By: Relevance
“…Interestingly, CREBBP at risk locus chr16:3606788-4606788, which scored in 2D, 3D and in vivo screens as a tumor-suppressor gene, was strongly connected with the same cluster suggesting that CREBBP regulates the SWI/SNF complex. This is consistent with previous reports of CREBBP function 47,48 . Furthermore, in agreement with the results described above, we found that DUSP4 has an expression signature similar to components of the MAPK signaling pathway.…”
Section: Survival Analysis In Cancer Patients Confirms Directionality and Cancer Association Of Bc Risk Genessupporting
confidence: 94%
“…Interestingly, CREBBP at risk locus chr16:3606788-4606788, which scored in 2D, 3D and in vivo screens as a tumor-suppressor gene, was strongly connected with the same cluster suggesting that CREBBP regulates the SWI/SNF complex. This is consistent with previous reports of CREBBP function 47,48 . Furthermore, in agreement with the results described above, we found that DUSP4 has an expression signature similar to components of the MAPK signaling pathway.…”
Section: Survival Analysis In Cancer Patients Confirms Directionality and Cancer Association Of Bc Risk Genessupporting
confidence: 94%
“…Interestingly, CREBBP at risk locus chr16:3606788-4606788, which scored in 2D, 3D and in vivo screens as a tumor-suppressor gene, was strongly connected with the same cluster suggesting that CREBBP regulates the SWI/SNF complex. This is consistent with previous reports of CREBBP function (Alver et al, 2017;Mathies et al, 2020). Furthermore, in agreement with the results described above, we found that DUSP4 has an expression signature similar to components of the MAPK signaling pathway.…”
Section: Hichip and Crisprqtl Validate Distal Regulation Between Bc Risk Loci And Genessupporting
confidence: 93%
“…3, E and F). cbp-1 encodes the C. elegans ortholog of histone acetyltransferase p300/CBP that promotes gene transcription (35)(36)(37)(38)(39)(40)(41)(42)(43). RNAi against many of the known genes encoding heat-responding transcription factor, including hsf-1, hsf-2, hif-1, and nhr-49, did not block TSP-1::GFP up-regulation (table S1).…”
Section: Resultsmentioning
confidence: 99%